GAGASAN MODEL ALTERNATIF PENYELESAIAN PERKARATINDAK PIDANA PENCURIAN DENGAN MENERAPKAN KONSEP RESTORATIF JUSTICE DIKAITKAN DENGAN PERATURAN MAHKAMAH AGUNG NOMOR 2 TAHUN 2012 TENTANG PENYESUAIAN BATASAN TINDAK PIDANA RINGAN DAN JUMLAH DENDA DALAMKUHP - Yunharadi muhammad azizi (Fakultas Hukum Universitas Riau, 2019)
Position of Supreme Court Regulation No. 2 of 2012 concerning Adjustment of Limits of Mild Crime and Number of Fines in the Criminal Code in the Criminal Justice System in Indonesia, its existence has been clear where the existence of the Supreme Court Regulation is one type of legislation. The Idea of Alternative Model of Settlement of Theft Crime Case by Applying the Restorative Concept of Justice Associated with the Supreme Court Regulation Number 2 of 2012 Concerning the Adjustment of Mild Criminal Actions and the Amount of Fines In the Criminal Code which is appropriately related to the renewal of criminal law is the punishment of social offenders.